Teacher Ethics Perspective Syed Naquib Al-Attas and KH. M. Hasyim Asy'ari - Muhamad Arif (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This study wants to reveal in detail the teacher's ethics according to two different points of view. First, the point of view of the leader of Islamic education reformer Syed Naquib Al-Attas Malaysia. Second, is the figure of Indonesian Islamic education, KH. M. Hasyim Asy'ari Indonesia. The research method used is a literature study combined with content analysis. So the answer is that the teacher ethics perspective of Syed Naquib Al-Attas and KH. M. Hasyim Asy'ari has differences in the details. However, it has a similar goal, namely to strengthen the transfer of knowledge that is strongly connected with the transfer of attitude (Adab/Akhlak).